Biocontrol potential of fungal chitinase from high yielding trichoderma viride against corcyra cephalonica (stainton) - NITHIN VIJAYAKUMAR; SANGILIMUTHU ALAGAR; NALINI MADANAGOPAL (International Journal of Pharma and Bio Sciences, 2017)
In this study we reported the screening of ten different fungal isolates for higher chitinase yield and its effect against the stored pest Corcyra cephalonica as natural bio-control agent without toxic effects. Different fungal strains were cultured and screened the chitinase activity for the production of chitinase enzyme. The majority of the farmers profoundly rely on synthetic pesticides for the eradication of stored food pests. These synthetic pesticides are leaving a very large amount of toxic residue in the environment which is harmful to human beings. Due to these toxic effects of synthetic pesticide we attempted to find the biological control agent against stored pests. From the fungal populations, ten different fungal species were used to screen for the higher production of chitinase. The chitinase was partly purified by ammonium sulfate precipitation method and was evaluated for its anti-feedant and growth inhibitory activities against the stored food pest Corcyra cephalonica Stainton at 62.5, 125, 250, 500 and 1000 ppm enzyme concentrations. Trichoderma viride shows a maximum chitinase activity of 2.75±0.029 U.mL-1 colloidal chitin on the sixth day. Next to Trichoderma viride, Metarhizium anisoplea and Candida albicans shows a chitinase activity of 2.51±0.031 and 2.23±0.070 U.mL-1 Colloidal chitin respectively. Treatment of Corcyra cephalonica with the partially purified chitinase from Trichoderma viride reduced the normal larval development according to a dose-dependent manner. This study shows Trichoderma viride chitinase can affect the growth of Corcyra cephalonica larvae. The outcome necessitates further insect bioassays and detection of underlying mechanisms.